2020
DOI: 10.1113/jp279759
|View full text |Cite
|
Sign up to set email alerts
|

New insights into resting and exertional right ventricular performance in the healthy heart through real‐time pressure‐volume analysis

Abstract: Key points Despite growing interest in right ventricular form and function in diseased states, there is a paucity of data regarding characteristics of right ventricular function – namely contractile and lusitropic reserve, as well as ventricular‐arterial coupling, in the healthy heart during rest, as well as submaximal and peak exercise. Pressure‐volume analysis of the right ventricle, during invasive cardiopulmonary exercise testing, demonstrates that that the right heart has enormous contractile reserve, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…Cornwell et al . (2020) have demonstrated that systolic RV performance in healthy volunteers can augment up to 3‐fold, which advances observations from patient controls (Spruijt et al . 2015).…”
Section: Methodological Considerationssupporting
confidence: 62%
See 1 more Smart Citation
“…Cornwell et al . (2020) have demonstrated that systolic RV performance in healthy volunteers can augment up to 3‐fold, which advances observations from patient controls (Spruijt et al . 2015).…”
Section: Methodological Considerationssupporting
confidence: 62%
“…Cornwell et al . (2020) have contributed to filling these knowledge gaps in a recent article in The Journal of Physiology . The study aimed to comprehensively describe systolic and diastolic RV performance and reserve in healthy individuals using pressure‐volume relationships at rest and during exercise.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The RV can quickly adapt to increases in O 2 demand by increasing coronary blood flow and increasing O 2 extraction. Clinically, this has recently been elegantly demonstrated in healthy adults using RV conductance catheters to collect real-time pressurevolumes loops (Cornwell et al, 2020). The authors found that resting RV energy expenditure was markedly lower than that of the resting LV and that RV energy expenditure increased dramatically with exercise to levels comparable with the resting LV.…”
Section: In Vivo Function Of the Healthy Adult Rvmentioning
confidence: 97%
“…29 Hypoxia-mediated augmentations in PAP lead to an increase in RV afterload. 6,[34][35][36][37][38][39][40] In a study of healthy individuals, RV end-diastolic volume increased from 52 ± 12 to 61 ± 25 mL at SL to 5085 m, respectively, which coincided with increases in systolic PAP (13.1 ± 5.9 versus 26.6 ± 10.8 mm Hg). 37 In another study, TAPSE declined from 2.9 ± 0.3 to 2.3 ± 0.3 from SL to 5050 m. 29 Finally, pharmacologic reductions of PAP by administration of sildenafil led to an increase in LV SV.…”
Section: Cardiopulmonary Hemodynamics Of Exercise At High Altitudementioning
confidence: 99%
“…39 In total, these data suggest that, as PAP (and hence, RV afterload) rises, RV contractility declines over time, and this reduction in RV function compromises LV SV. Further research incorporating invasive and comprehensive assessments of RV function-such as has recently been performed in patients with pulmonary arterial hypertension, 41 heart failure with preserved ejection fraction, 42 heart failure patients supported by LV assist devices, 43 and even healthy individuals exercising at SL 40 -is necessary to characterize the effects of acute and chronic altitude exposure on resting and exertional RV performance and how decrements in RV function may influence LV SV, Qc, and exercise capacity overall.…”
Section: Cardiopulmonary Hemodynamics Of Exercise At High Altitudementioning
confidence: 99%